Exploring the Role of Authentic Materials in Reading Instruction: Students' Perceptions, Preferences, and Comprehension Outcomes - Taslimah, Asti; Arifin, Syaadiah (IKIP Siliwangi, 2025)
The integration of authentic materials in reading lessons has gained significant attention in the context of English as a Foreign Language (EFL) classroom, as these materials provide real-world language exposure that enhances comprehension and motivation. Despite their advantages, many students face challenges in understanding authentic texts due to unfamiliar vocabulary, complex sentence structures, and lack of proper reading strategies. This study aims to explore high school students' perceptions and preferences regarding the use of authentic materials in reading lessons, identifying both the benefits and challenges encountered. A qualitative case study design was employed, involving 20 high school students from South Tangerang, using classroom observations, open-ended questionnaires, and semi-structured interviews for data collection. The findings reveal that students perceive authentic materials positively, appreciating their relevance and ability to engage learners with real-world content. However, challenges such as difficult vocabulary and complex structures were highlighted. Students preferred illustrated materials like comics, magazines, and short stories, while finding academic articles and newspapers difficult. The study suggests that while authentic materials can enhance engagement and motivation, their effectiveness depends on careful selection aligned with students' proficiency levels. It recommends that educators provide scaffolding, teach reading strategies, and adopt a balanced approach by combining authentic and simplified materials for optimal learning outcomes.